2007
DOI: 10.1007/s10661-007-9623-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of some heavy metal pollution with environmental and microbiological parameters in sub-basin of Kocabas Stream (Biga, Canakkale, Turkey) by ICP-AES

Abstract: Waste water pollution in industrial areas is one of the most important environmental problems. Heavy metal pollution, especially chromium species in waste water sources from tannery affects our lives. Kocabas Stream is located in south-west Marmara region and Biga town is positioned in the sub basin on the stream. This water source functions as the water for irrigation in agriculture, drinking water for animals and for human use. Thus, this study is of great importance. Waste water pollution can affect all eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Positive loadings on temperature, conductivity, TDS, total Pb, and total Zn; and negative loading of FC were observed in the PCA. This agrees well with the previous studies that increase in temperature (Chigbu et al 2004;Noble et al 2004), salinity (Hamzah et al 2011;Yayintaş et al 2007), and heavy metals (Malik and Ahmad 2002;Jana and Bhattacharya 1988) were harmful to FC survival in natural environments. Besides, the negative loadings on FC, turbidity and TSS are not surprising.…”
Section: Principal Component Analysissupporting
confidence: 93%
“…Positive loadings on temperature, conductivity, TDS, total Pb, and total Zn; and negative loading of FC were observed in the PCA. This agrees well with the previous studies that increase in temperature (Chigbu et al 2004;Noble et al 2004), salinity (Hamzah et al 2011;Yayintaş et al 2007), and heavy metals (Malik and Ahmad 2002;Jana and Bhattacharya 1988) were harmful to FC survival in natural environments. Besides, the negative loadings on FC, turbidity and TSS are not surprising.…”
Section: Principal Component Analysissupporting
confidence: 93%
“…The Concentration of all the metals is higher in plankton from both seasons. The result was similar to that reported by Yayintas et al [24]. In the present study, abiotic parameters such as temperature, pH and dissolved oxygen were observed very low at Retteri and Velachery Lake.…”
Section: Discussionsupporting
confidence: 93%
“…The voltammetric method was firstly used to determine the concentration of Cd and Pb in seawater (Neeb 1959). Recently, anodic stripping voltammetry was also used to this purpose (Zirino et al 1973;Abdullah et al 1976;Gillain et al 1979;Jurado-Gonzelez et al 2003;Van den Berg 1986).…”
Section: Introductionmentioning
confidence: 99%